Analysis of the Frost-Induced Damage of Building Enclosures on the Territory of the Czech Republic - Jan Kočí; Jiří Maděra; Vojtěch Pommer; Robert Černý (Advances in Materials Science and Engineering)
A comprehensive analysis of environmental loads across the Czech Republic in terms of frost-induced damage is presented. Computational simulation of hygrothermal performance of eleven characteristic types of building envelopes, composed of both contemporary and historical materials, is performed at first. The exterior boundary conditions of the computational model are defined by a set of weather data characterizing the environmental conditions in the Czech Republic, which are acquired from 64 weather stations. The results of hygrothermal simulations are assessed using several specific damage functions. In this way, the basic datasets for the frost damage analysis are obtained. Their application as input parameters of a specially developed correction procedure based on elevation makes them possible to obtain a continuous coverage of the geographic area of the Czech Republic. Finally, isopleths of the supposed frost damage are drawn, depending on the envelope type, and damage maps are produced which may help the engineers to enhance the building envelope design process. The presented results indicate the necessity of paying attention to local environmental loads in the building enclosure design process and reveal both critical and favorable locations from the point of view of frost-induced damage to buildings.